Probable occurrence of ecdysteroid fatty acid esters in different classes of arthropods - Connat, Jean-Louis; Diehl, Peter-Allan (My University, 1986)
We investigated the fate of injected [3H]ecdysone or [3H]20-hydroxyecdysone in various species of ticks, spiders, scorpions, myriapods, crustaceans and insects. Most of these arthropods were able to convert the ecdysteroids to esterase-labile metabolites with a very apolar behaviour in reverse-phase HPLC. Some of them have retention times similar to the apolar conjugates AP2 of the tick, Ornithodoros moubata, which have been identified recently as ecdysteroids esterified as C22 with palmitic, stearic, oleic or linoleic acid [Diehl et al. (1985a) Int. J. invert. Reprod. Devl. 8, 1–13]. Others are less apolar and could correspond to the AP1 from O. moubata. The possible function of these metabolites remains to be established. They could represent inactivation products and/or a hormone storage-form for embryos.
Keywords: arthropods; ecdysteroid metabolism; apolar ecdysteroid conjugates